ALGORITHMIC OPTIMIZATION INFORMATION AND STRATEGIES FOR INCREASING THE REACH OF BEGINNER CREATOR ACCOUNTS ON FACEBOOK PRO IN INDONESIA - Chairul, Muhammad Ilham Firizkillah; Waskita, Arya Adhyaksa; Wiharjo, Sudarno; RA, Okta Reni Azrina (Asia Information System Journal, 2025)
The evolution of algorithmic systems on digital platforms has fundamentally transformed the logic of content distribution, shifting from chronological feeds to AI-driven recommendation ecosystems that act as active regulators of creator visibility. While discussions on algorithmic visibility are extensive for platforms like TikTok and Instagram, a significant research gap remains regarding the Indonesian creator ecosystem on Facebook Pro, particularly concerning how human–algorithm interaction shapes content performance. This study aims to analyze algorithm optimization strategies among beginner creators on Facebook Pro by examining the critical relationship between content format consistency, engagement velocity, and algorithmic distribution. Research Method: Adopting a qualitative-descriptive design, a case study was conducted on two Indonesian creator accounts—Muhammad Ilham Firizkillah and Sejenak Hening—representing contrasting storytelling-educational and motivational production paradigms. Primary data were collected from Facebook Pro Insights between July and October 2025, utilizing Python-based analytics to evaluate Reels performance, retention rates, and audience growth. The results indicate a striking contrast in performance: the Sejenak Hening account achieved an 876% increase in reach and 1.1 million views by maintaining consistent themes and visuals, allowing the algorithm to recognize stable patterns for exponential distribution. Conversely, the Ilham Firizkillah account saw a 52% decline in views due to high format variation and weak early interaction (2%), triggering algorithmic momentum decay. Findings confirm a perfect correlation (r = 1.00) between format stability and algorithmic reach. Implication and Recommendation: These findings emphasize that sustainable organic growth is determined by the synchronization between predictable upload patterns and the machine-learning system’s real-time evaluation of interaction efficiency. It is recommended that beginner creators prioritize the "three-second hook" to capture initial attention and maintain strict discipline in narrative and visual formats to build algorithmic credibility.